Back to Nature : The Green and the Real in the Late Renaissance - Watson, Robert N. (Book collections on Project MUSE., 2008)
Selected by Choice magazine as an Outstanding Academic TitleSweeping across scholarly disciplines, Back to Nature shows that, from the moment of their conception, modern ecological and epistemological anxieties were conjoined twins. Urbanization, capitalism, Protestantism, colonialism, revived Skepticism, empirical science, and optical technologies conspired to alienate people from both the earth and reality itself in the seventeenth century. Literary and visual arts explored the resulting cultural wounds, expressing the pain and proposing some ingenious cures. The stakes, Robert N. Watson demonstrates, were huge.Shakespeare's comedies, Marvell's pastoral lyrics, Traherne's visionary Centuries, and Dutch painting all illuminate a fierce submerged debate about what love of nature has to do with perception of reality.